Consumers' Concerns Regarding Product Quality: Evidence From Chinese Online Reviews. (March 2023) - Wang, Xian; Li, Huixian; Wang, Qingyi; Noble, Alison
Customers' concerns regarding product quality (CPQs), as expressed in online reviews, provide future customers with information that may influence their own purchase decisions. Recent research attaches considerable importance to consumers' emotions embedded in their language style, based on function words, but rarely touches on their CPQs, which are also embedded in their language style. Therefore, this study aims to examine the CPQs of Chinese women's clothes buyers. We build a corpus of 32, 667 words from the online reviews of women's clothes buyers on the Chinese website Taobao. A novel language inquiry word count dictionary for topic types related to product quality is built, which is then imported into a language style matching algorithm which assesses the synchrony of the language style. Our results show that buyers' CPQs are diverse and concentrated in scope; consumers' different expressions in online reviews are dependent on the sequence and impact factor of CPQs embedded in their language style. This study's findings offer companies valuable insights to identify customers' CPQs based on their language style, which may allow them to devise more effective promotion strategies and product designs.